Sensitivities-based method and expected shortfall for market risk under FRTB: Its impact on options risk capital - Carlos Alexander Grajales; Santiago Medina Hurtado (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This paper measures different market risk impacts on options portfolios under the new Fundamental Review of the Trading Book (FRTB) regulation, issued in Basel and coming into effect in 2023. Design/methodology/approach - This paper first suggests an algorithm for implementing the FRTB standardised approach via the sensitivities-based method to estimate a portfolio's risk capital and presents an illustration applied to an option position. Second, it proposes a methodology to estimate the expected shortfall in options portfolios from the FRTB internal models approach. In this regard, an application is developed to measure expected shortfall (ES) and value at risk (VaR) impacts under FRTB versus conventional VaR in a currency option position by considering stress scenarios from the 2007-9 and 2020-1 crises and back-testing procedures. Findings - The suggested algorithm satisfactorily captures impacts via the sensitivities-based method, and higher risk capital demands are expected for emerging economies. Also, the planned FRTB methodology to measure ES and VaR is appropriate; in particular, historical metrics perform well. Astonishingly, their revealed impacts are more significant under the 2020-1 pandemic crisis than the 2007-9 financial crisis. Originality/value - The proposals developed weave a communication bridge between the standardised and internal approaches of FRTB regulation, which can be scaled up technologically and institutionally.
Keywords: C5; G18; G32; 330; Fundamental Review of the Trading Book (FRTB); Sensitivities-based method; Expected shortfall; Market risk